2012
DOI: 10.1080/09603123.2011.634386
|View full text |Cite
|
Sign up to set email alerts
|

A geographical analysis of breast cancer clustering in southern Ontario: generating hypotheses on environmental influences

Abstract: This article presents the results of spatial analysis of breast cancer clustering in southern Ontario. Data from the Cancer Care Ontario were analyzed using the Scan Statistic at the level of county, with further analysis conducted within counties that were identified as primary clusters at the dissemination area level. The results identified five counties as primary clusters of women diagnosed with breast cancer between 1986 and 2002: Essex (relative risk [RR] =1.096-1.061; p<0.001), Lambton (RR=1.05-1.167), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Cancer incidence patterns vary in different populations and are associated with occupational, environmental, social, cultural, ethnic, geographic, nutritional and other unknown factors (12)(13)(14). Cancer distribution also varies in different provinces in the Islamic Republic of Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer incidence patterns vary in different populations and are associated with occupational, environmental, social, cultural, ethnic, geographic, nutritional and other unknown factors (12)(13)(14). Cancer distribution also varies in different provinces in the Islamic Republic of Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary factors are therefore clearly of importance. In addition, environmental conditions, including contamination levels may be important, as evidenced by clustering of disease (Lorenzo-Luaces Alvarez et al, 2009;Luginaah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A recent Canadian study applied the scan statistics of SaTScan and found excess incidence rates of breast cancer in five counties in southern Ontario, which were suggested related to environmental pollution from industry and farming characterising these areas [17]. The study was based on aggregated incidence data and results should therefore be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have used disease mapping and spatial analyses in the search for environmental factors that could be related to breast cancer, however many of these studies relied on aggregated data and used space-only approaches by only including one location to record health events e.g. place of residence at date of diagnosis or date of death [16,17]. However, chronic diseases such as cancer develop over long time, thus causative exposure could occur many years prior to disease manifestation and during that time, individuals may have moved to new addresses several times.…”
Section: Introductionmentioning
confidence: 99%